Utilization of Information Technology (IT) in Micro, Small and Medium Enterprises (MSMEs) by Women Business Actors in Pesawaran Regency - Putri, Aniza; Gitosaputro, Sumaryo; Syarief, Yuniar Aviati; Rangga, Kordiyana K.; Silviyanti, Serly (International Journal of Scientific Research and Management (IJSRM), 2025)
The utilization of information technology (IT) has become an important factor in increasing the efficiency and competitiveness of the Micro, Small and Medium Enterprises (MSMEs) sector.  The purpose of this study was to determine the level of IT utilization by women business actors in Pesawaran Regency in their daily business activities.  This research was conducted in Pesawaran Regency. Data collection in this study was conducted in April-June 2025.  Respondents in this study were 97 female MSME players operating in the region.  The method in this study used a survey method and the research location was determined purposively with a quantitative descriptive approach.  The results showed that the majority of respondents, 52 people (53.60 percent), were classified in the “moderately intensive” category.  Women business owners have recognized and used digital communication platforms such as WhatsApp and Facebook to support their business activities, especially in promotion and interaction with customers.  However, utilization of more complex business applications such as marketplaces, digital bookkeeping software, and content-based marketing strategies is still low.  Key barriers include limited digital literacy, access to technology tools, and low participation in supporting training.